COMSKIL: a communication skills training program for medical students - Gebhardt, Claudia (GMS J Med Educ, 2021)
Objectives: Training communication skills has come to be recognized as a vital aspect of medical school education. A medical communication course based on the COMSKIL Communication Skills Training (CST) Program was developed, integrated into the core curriculum, and evaluated at the Leipzig University Medical School. Methods: Between October 2016 and July 2017, 312 medical students (mean age 21.80 years; 62% male) participated in the medical communication course. Each course unit was evaluated via questionnaires specifically designed to address the theoretical and practical content of the curriculum. The items correspond to the material covered in each course unit. Students responded using a 5-point-Likert scale (1=“not at all helpful”, 5=“extremely helpful”) to rate the degree to which the course helped them learn about the subject matter and train the skills covered in the curriculum. Results: The average score for the first part of the course (theoretical foundations) was M=3.69 (SD=0.35). The second part received a similar rating (M=3.84; SD=0.73). The role play exercises with actor-patients received a score of M=4.27 (SD=0.62). In an overall evaluation at the end of the course, students rated the administration of the course (setting, etc), knowledge gained, and skills trained with a score of M=4.11 (SD=0.66). The role play exercises received an overall score of M=4.36 (SD=0.61). Conclusion: A new curriculum for teaching medical students patient-physician communication skills based on the COMSKIL CST program was established at the University of Leipzig. The goal of this course is to teach students about the kinds of communication scenarios they will encounter in their future working lives as care providers and equip them with the fundamental communication techniques and skills they need to successfully handle those situations. A formal evaluation of the program resulted in satisfactory findings, indicating that it is well suited for use in medical universities.